Exploration of antioxidant and antimicrobial potential of methanolic extract of root stock of Premna herbacea - Isha Dhamija; Nitesh Kumar; K.S.R. Pai; M. Manjunath Setty; Sandeep Kumar; Asim K. Jana (Bangladesh Pharmacological Society, 2014)
No abstract is available